2016
DOI: 10.1097/wnr.0000000000000646
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and biochemical effects of ketamine and dextromethorphan relative to its antidepressant-like effects in Swiss Webster mice

Abstract: Ketamine has been shown to produce rapid and robust antidepressant effects in depressed individuals, however its abuse potential and adverse psychotomimetic effects limit its widespread use. Dextromethorphan may serve as a safer alternative based on pharmacodynamic similarities to ketamine. In this proof of concept study, behavioral and biochemical analyses were undertaken to evaluate the potential involvement of brain derived neurotrophic factor (BDNF) in the antidepressant-like effects of dextromethorphan in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 40 publications
(95 reference statements)
3
10
1
Order By: Relevance
“…Ketamine increased the BDNF expression in the BLA and IL-PFC in a short period of time (*2 h) after administration, which is consistent with a previous study showing that 1 h-5 h are sufficient for significant upregulation of protein expression [40]. A recent study confirmed that ketamine increases pro-BDNF expression within 40 min after a single dose [41]. These results indicate that ketamine might prevent the degradation of protein or enhance the expression of protein via the cytoplasmic mRNA pool.…”
Section: Discussionsupporting
confidence: 89%
“…Ketamine increased the BDNF expression in the BLA and IL-PFC in a short period of time (*2 h) after administration, which is consistent with a previous study showing that 1 h-5 h are sufficient for significant upregulation of protein expression [40]. A recent study confirmed that ketamine increases pro-BDNF expression within 40 min after a single dose [41]. These results indicate that ketamine might prevent the degradation of protein or enhance the expression of protein via the cytoplasmic mRNA pool.…”
Section: Discussionsupporting
confidence: 89%
“…Considering that the above report of Po et al (2015) that also used male rats, we posit that males may be more prone to DM-induced depressive-like behaviors. However, recent Swiss Webster mice studies findings are in contrast with the results of the present study (Nguyen et al, 2016;Nguyen & Matsumoto, 2015). These authors reported that DM reduced immobility time in the FST and TST, indicating the antidepressant effect.…”
Section: Discussioncontrasting
confidence: 99%
“…Although DM has been shown to produce rapid antidepressant activity in various mice studies (Nguyen et al, 2016;Nguyen & Matsumoto, 2015), according to our research, DM induces a depression-like state in the DM-treated rats, notwithstanding treatment dose or gender of rats. The state of depression in animals was assessed by the TST.…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, although no behavioral outcome was measured, a ketamine infusion at an analgesic dose (10 mg/kg, IV, 2 h) increased BDNF protein in the amygdala of rats; this effect was dose-dependent and not seen with a 40 mg/kg infusion [ 40 ]. The inconsistent effects of ketamine administration on BDNF levels in the brain may be due to the timing of the BDNF assay, because BDNF levels may fluctuate following ketamine administration [ 41 ]. Overall, studies reporting decreased fear memory after ketamine implicated increased BDNF in this effect, but it is worth noting that changes in BDNF are dose- and time-dependent.…”
Section: Molecular Mechanismsmentioning
confidence: 99%